2007
DOI: 10.1074/jbc.m609374200
|View full text |Cite
|
Sign up to set email alerts
|

Burst Kinetics and Redox Transformations of the Active Site Manganese Ion in Oxalate Oxidase

Abstract: Oxalate oxidase (EC 1.2.3.4) catalyzes the oxidative cleavage of oxalate to carbon dioxide and hydrogen peroxide. In this study, unusual nonstoichiometric burst kinetics of the steady state reaction were observed and analyzed in detail, revealing that a reversible inactivation process occurs during turnover, associated with a slow isomerization of the substrate complex. We have investigated the underlying molecular mechanism of this kinetic behavior by preparing recombinant barley oxalate oxidase in three dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 45 publications
4
37
0
Order By: Relevance
“…The K M value for acetaldehyde substrate and PQQ-AldDH enzyme has been shown to be 3.3 mM in the literature [36]. The literature value for K M for the natural substrate oxalic acid and oxalate oxidase enzyme is 0.78 mM [30]. The K M values determined for all three immobilized enzyme with their non-natural substrates were lower than the values reported in the literature for free enzyme in solution indicating that the K M for the non-natural substrate is different for these enzymes immobilized on the electrodes.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The K M value for acetaldehyde substrate and PQQ-AldDH enzyme has been shown to be 3.3 mM in the literature [36]. The literature value for K M for the natural substrate oxalic acid and oxalate oxidase enzyme is 0.78 mM [30]. The K M values determined for all three immobilized enzyme with their non-natural substrates were lower than the values reported in the literature for free enzyme in solution indicating that the K M for the non-natural substrate is different for these enzymes immobilized on the electrodes.…”
Section: Resultsmentioning
confidence: 98%
“…Both PQQ-dependent enzymes undergo a 6e-process from the hemes and the PQQ when there is no substrate present [29]. Oxalate oxidase undergoes a 2e-process when substrate is not present [30]. The amount of enzyme cast and the amount of enzyme electrochemically accessible for each is shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(6) The structure of OxOx (Woo et al, 2000) contains a manganese ion bound to the side chains of conserved glutamate and histidine residues in a site that is located toward the narrow end of the barrel-like domain. Studies by Whittaker and coworkers (Whittaker et al, 2007) have suggested that the catalytically active form of OxOx is likely the Mn III form and not the Mn II form as was previously thought. In this mechanism (Scheme 8), the active, resting Mn III enzyme binds oxalate (step 1) as the monoanion to form an enzyme-substrate complex.…”
Section: Oxalate Oxidase (Pdb: 1fi2)mentioning
confidence: 85%
“…The interception of a carbon dioxide radical anion intermediate by dioxygen during OxOx turnover would generate a second molecule of carbon dioxide and superoxide (step 4). Electron transfer oxidation of Mn II to Mn III by the protonated superoxide (step 5) involving either an inner-sphere or outer-sphere mechanism would generate hydrogen peroxide (Whittaker et al, 2007). This scheme predicts that one proton is consumed per turnover cycle and that peroxymonocarbonate is not formed as a primary product , although the presence of both peroxide nucleophile and carbon dioxide electrophile in the product mixture makes it likely that peroxymonocarbonate (a peracid) will be produced as a secondary product in solution.…”
Section: Oxalate Oxidase (Pdb: 1fi2)mentioning
confidence: 99%